Enabling Content Distribution in Vehicular Ad Hoc Networks - Luan, Tom H.; Shen, Xuemin (Sherman).; Bai, Fan.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
This SpringerBrief presents key enabling technologies and state-of-the-art research on delivering efficient content distribution services to fast moving vehicles. It describes recent research developments and proposals towards the efficient, resilient and scalable content distribution to vehicles through both infrastructure-based and infrastructure-less vehicular networks. The authors focus on the rich multimedia services provided by vehicular environment content distribution including vehicular communications and media playback, giving passengers many infotainment applications. Common problems of vehicular network research are addressed, including network design and optimization, standardization, and the adaptive playout from a user’s perspective.
Introduction -- Medium-size Content Distribution using an Infrastructure-based Approach -- Medium-size Content Transmission over Infrastructure-less Inter-vehicle Communications -- Large-volume Content Distribution in Vehicular Networks: Adaptive Playout from User's Perspective -- Conclusion.
Keywords: Computer communication systems; Electrical engineering; Application software; Power electronics; Computer Communication Networks; Communications Engineering, Networks; Information Systems Applications (incl. Internet).; Power Electronics, Electrical Machines and Networks